Islamic art - Mozzati, Luca. (Munich ; London ; New York)
319 sayfa
Keywords: “This gorgeous survey of art from the Islamic world covers three continents and fourteen centuries. From its birth in the 7th century through modern times, the Islamic religion has inspired glorious works of art. This stunning book includes more than four hundred reproductions of treasures of Islamic art that span the world: from southern Europe, along the entire Mediterranean basin to sub-Saharan Africa through the Middle East, India, and Central Asia. Arranged geographically, the objects include paintings, miniatures, ceramics, calligraphy, textiles, carpets, and metal works. Each region is given a thorough introduction that offers historical context and extensive descriptions of its artifacts. Accompanying essays offer guidance in interpreting the many themes that tie these works together, including typology, calligraphy, and religious beliefs. With its large format, exquisite reproductions, and extensive research, this book is a thorough introduction to the Islamic artistic tradition“ --